The effects of acute hypoxia on cognitive and cardiovascular parameters in healthy subjects - Rajeevlochan Ravi; Mirza M. F. Subhan (Academia Biology)
Background: Hypoxia can affect the health and safety of patients and persons in various occupations. There is uncertainty surrounding the effect acute hypoxia may have on cognition and the cardiovascular system.